PERLINDUNGAN KORBAN DAN SAKSI DALAM PELANGGARAN HAK ASASI MANUSIA YANG BERAT ( UNDANG-UNDANG NOMOR 26 TAHUN 2000 TENTANG PENGADILAN HAK ASASI MANUSIA ) - Sadia Dwi Ratmaja, I Gede; Keneng, I Ketut; Sudjana, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Indonesiais a country oflaws thatgovernedtheconstitutionin 1945. In Indonesiathere are manyviolations committedby governments and society. One of the offensesthat needtoget their attention andresolutionarecasesof humanrights violationsare heavy. In the eyes ofthe international community,Indonesiaconsidered lessattention tohuman rightsviolationsparticularlysevere.In Indonesia,rightsareregulated insomelegislation. Legislationin question, among others, Law No.39 Year1999 onHumanRights.To handle thecases ofhuman rightsviolationsThe heavymoldedLaw No.26 Year2000 onHuman Rights Court. Lawnotprovide justiceto victimsand witnesses. So toshowthe seriousness of thegovernmentissuedGovernment Regulation No.2 of 2002on Procedures forthe Protection ofVictimsandWitnessesManusisaRights ViolationsInTheWeight. In additionitalsoformedgovernmentregulationNo. 3 of 2002on Compensation, Restitution, andRehabilitationAgainstVictimsof Human Rights ViolationsThatWeight. The enactmentis expectedrights of victimsand witnesses inhuman rights abusesTheweightcan be felt bothat the stage ofinquiry, investigation, prosecution, during andafter atrialconducted. In government regulationsthere are someweaknessesthat needto get asettlementfrom the government, bothofnorms andprocedures for grantingprotection.sowith improvementsin the regulationto provide protectionand fulfillment ofthe rights of victimsand witnessesoptimally.
Keywords: protection, victims and witnesses, human rights, the serious human rights violations